Growing Importance of Internet of Things (IoT) in the Modern Age (International Journal of Food and Nutritional Sciences, 2022)
People who make use of things are able to live and work more shrewdly and with complete control over their lives. The Internet of Things (IoT) is crucial to businesses because it offers cutting-edge home administration innovations. The Internet of Things, a comparatively recent invention, is a global network of devices that can communicate and exchange information with one another through the Internet. There are several differences between the Internet and the Internet of Things. The linked items' data may be used by the Internet of Things to develop, evaluate, and make choices. The author discussed the applications f IoT which they use in their day to day life and make their life easier. Further, challenges for IoT in the modern age discussed by the researcher. This study focuses on the growing impacts of Internet of Things in the modern environment. The findings conclude that IoT adoption at scale in the future made great contributions to greater levels of employee engagement, which in eventually caused to: Productivity improvement, work satisfaction, effectiveness, as well as enhanced customer service.